Precariousness Profile and Career Adaptability as Determinants of Job Insecurity: A Three-Wave Study. (April 2020) - Urbanaviciute, Ieva; Udayar, Shagini; Maggiori, Christian; Rossier, Jérôme
The present study compares the mean levels and growth in job insecurity across employees' precariousness profiles as defined by a combination of perceived employability and financial difficulties. Drawing on the labor market precariousness and workplace stress literature, we hypothesized that employees with the most precarious profile would report elevated levels of job insecurity followed by a growth trend. Moreover, career adaptability was expected to act as a resource for counteracting job insecurity. The study was based on three waves of a longitudinal "Professional Paths" survey (National Centre of Competence in Research LIVES) conducted in Switzerland. The data of 799 professionally active adults were analyzed using latent growth modeling. In line with our hypothesis, the findings showed the highest levels of job insecurity and the most pronounced growth trend among employees with the precarious profile. Interestingly, different career adaptability facets played differing roles in predicting job insecurity, potentially revealing some of its under-researched aspects.